2019
DOI: 10.31661/jbpe.v0i0.1047
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Knee Prosthesis in Patients’ Body on Radiation Dose Distribution: A Monte Carlo Approach

Abstract: Introduction: Metal prostheses in patients affect the radiotherapy dose distribution. Metal prostheses with high density and atomic number cause major changes in scattering and attenuation of radiation. The present study aims to assess the impact of metal knee prosthesis with various dimensions and materials on radiotherapy dose distribution. Material and Methods: In this research, the Varian Linac and water phantom were simulated using the MCNPX code. Dose distribution of photon beam in a water phantom, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Carolan et al [22] has highlighted the increase in dose on the distal surface of the prosthesis approximately 35%. The study conducted by Bayatiani et al [23] also suggested the decrease in dose to the areas which were completely blocked by the metal prosthesis. In addition, the scattering of the beam from the metal surface increases the dose in femoral bone and nearby healthy tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Carolan et al [22] has highlighted the increase in dose on the distal surface of the prosthesis approximately 35%. The study conducted by Bayatiani et al [23] also suggested the decrease in dose to the areas which were completely blocked by the metal prosthesis. In addition, the scattering of the beam from the metal surface increases the dose in femoral bone and nearby healthy tissues.…”
Section: Discussionmentioning
confidence: 95%